Peran Dewan Pengawas Syariah dalam Kepatuhan Prinsip Syariah pada Pelaksanaan Good Corporate Governance - Shalihin, Rijalush; Shalihah, Bunga Mar'atush; Ariadi, Purmansyah; Rulitawati (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The purpose of this study is to find out how the role of the Sharia Supervisory Board in complying with sharia principles applied in sharia banking is based on good corporate governance. The method used in this research is using field research. Qualitative descriptive approach. The source of data in this study is secondary data. Data collection techniques are documentation through journals, books, libraries and the Qur'an and Hadith. The findings obtained in this study are that as an intermediary institution based on sharia principles, Islamic banks must comply with two types of compliance, namely sharia principles and legal compliance. The application of such compliance is not only required for good corporate governance and various Islamic bank products, but also for financial deeds made by a notary. Therefore, financial actions in Islamic banks must reflect the principles of sharia compliance, not only legal compliance. Specific concerns regarding sharia compliance have come within the scope of the Sharia Supervisory Board's authority. The Sharia Supervisory Board has implemented good sharia compliance in sharia banking. Islamic banking has implemented Good Corporate Governance (GCG) this triggers that every transaction and financial arrangement in Islamic banking is in accordance with sharia principles.